PENGARUH LAYANAN APOTIK TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT X GADING SERPONG TANGERANG: THE EFFECT OF PHARMACY SERVICES ON PATIENT SATISFACTION AT X GADING HOSPITAL SERPONG TANGERANG - Dedi Supriadi; Leo Alexander Tambunan, S.E,M.M (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
Quality greatly affects patient satisfaction, where the patient will feel satisfied if the patient's perception of the quality of service is as expected by the patient. And will feel dissatisfied if the quality of service is not as expected. With the results of minimal service quality, of course, patient satisfaction is also not optimal. Therefore, this study aims to determine the effect of physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), attention (empathy), and assurance (assurance) on patient satisfaction. The population in this study were all patients at the X Hospital, Gading Serpong , South Tangerang, totaling 180 people. The researcher used the Heir sampling technique. Analysis of the data in this study using a multiple regression models. The results of this study indicate that physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), attention (empathy), and assurance (assurance) to patient satisfaction. Keywords: Tangible ,Reliability, Responsivenes, Empathy, Assurance.